American Economic Association Committee on Statistics (AEAStat) Annual Report—2011 - Feenstra, Robert (American Economic Review, 2012)
Membership during 2011: Robert Feenstra, University of California, Davis, Co-chair; Alan Krueger, Princeton University, Co-chair (until fall 2011); Dennis Fixler, Bureau of Economic Analysis; Barbara Fraumeni, University of Southern Maine; David S. Johnson, Census Bureau; Jonathan A. Parker, Northwestern University; Charles Schultze, Brookings Institution; Mark Bils, University of Rochester; Randall Kroszner, University of Chicago.